Optimizing task offloading and resource allocation in a multi-layer fog computing network - Bairi, Sahitya (Nanyang Technological University, 2023)
This research studies the current solutions present to develop a joint offloading and resource allocation framework for a multi-later fog-computing network. Specifically, this research studies the problem defined, and solutions presented in the paper titled “Optimal Energy Efficiency with Delay Constraints for Multi-Layer Cooperative Fog Computing Network”. The Project gives an implementation of the Feasibility Finding Benders Decomposition (FFBD) algorithm presented in the paper and compares it with the default Gurobi MIP solver for solving the same problem. CloudSim is also explored to visualize the offloading and resource allocation results of the Problem in a Cloud Environment.